Histopathological study on some form of bovine pneumonia - MAHDI THWENI (University of Thi-Qar Journal of Science, 2019)
A total of 1234 cow lungs were examined grossly fromapparently healthy adults cows slaughtered at Basra during theperiod from January 2005 to June 2005.Tissue from pneumonia lungs were collected processedsectioned at5- 6µ and stained for histopathological study conductedon 127 consolidated lungs of adult cows.Pneumonia has been classified according to the type ofinflammatory and pulmonary reaction as well as the lesionduration. Pneumonia in the descending order of prevalence werechronic interstitial pneumonia, fibrinous pneumonia,fibrinopurulent pneumonia, acute suppurative pneumonia,lymphoid pneumonia and chronic pneumonia .The prevalence of pneumonia in adult cows on the basis ofhistopathological examination in this study was 9.5%, the role ofthe such lesion in cows were discussed.